Circulating tumour cells and tumour biomarkers in functional midgut neuroendocrine tumours. (7th February 2022) - Meyer, Tim; Caplin, Martyn; Khan, Mohid S.; Toumpanakis, Christos; Shetty, Shishir; Ramage, John K.; Houchard, Aude; Higgs, Kate; Shah, Tahir
Abstract: CALM‐NET was a phase IV exploratory study in the UK that aimed to evaluate if the presence of circulating tumour cells (CTCs) at baseline predicted symptomatic response in patients with midgut neuroendocrine tumours (NETs) treated with lanreotide autogel (LAN). Adults with functional, well/moderately differentiated (Ki‐67 <20%) midgut NETs received LAN 120 mg/28 days for 1 year. CTCs were present in blood if enumeration was >0. Primary endpoint was the clinical value of baseline CTCs to predict symptomatic response (decrease in diarrhoea or flushing of ≥50% frequency, or ≥1 severity level). Other endpoints included progression‐free survival (PFS) and correlations between plasma and urinary biomarkers (including 5‐hydroxyindoleacetic acid [5‐HIAA]). Fifty patients were enrolled; 40 completed the study. Baseline CTCs were present in 22 (45.8%) patients (missing baseline CTC status n  = 2). Overall, 87.5% (95% confidence interval [CI]: 73.9; 94.5) of patients had a symptomatic response; a 5.9‐fold higher odds of symptomatic response in patients without CTC versus patients with CTC at baseline was observed, although this was not statistically significant (odds ratio: 0.17 [95% CI: 0.02; 1.65], p  = .126). One‐year PFS rate was 66.4% (95% CI: 48.8; 79.2). Biomarker concentrations did not correlate to baseline CTC status. However, there was a strong correlation between plasma and urinary 5‐HIAA (Spearman correlation coefficients ≥0.87 [ p  < .001], all time points). In conclusion, patients without CTC at baseline may be more likely to achieve a symptomatic response following LAN treatment than patients with CTC. Plasma 5‐HIAA correlated with urinary 5‐HIAA during LAN treatment. ClinicalTrials.gov identifier: NCT02075606. Abstract : CALM‐NET was a phase IV exploratory study designed to evaluate if the presence of circulating tumour cells (CTCs) could be used to predict symptomatic response in patients with midgut neuroendocrine tumours (NETs) treated with lanreotide autogel (LAN). The results of the primary endpoint, clinical value of baseline CTCs to predict symptomatic response, showed that patients who were CTC‐negative achieved a response rate of 95.5%, compared with 77.8% for patients who were CTC‐positive (odds ratio: 0.17, 95% CI: 0.02; 1.65). The symptomatic response did not differ between patients with baseline CTCs and those without; however, the study was limited as a result of its small sample size. Clinical symptomatic response rates (flushing and diarrhoea) in LAN‐treated patients according to CTC status. a Two patients had missing CTC data and eight patients had missing data for clinical symptomatic response (four who were CTC+ and four who were CTC−). Error bars depict the 95% CI. CI, confidence interval; CTC, circulating tumour cell; LAN, lanreotide autogel.